The ARVC causing TMEM43-p.S358L mutation has impact on the lipid metabolism. (10th June 2022) - Ratnavadivel, S; Klinke, N; Meyer, H; Paululat, A; Kassner, A; Gummert, J; Milting, H
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Deutsche Forschungsgemeinschaft (DFG) - Projektnummer 450999875 Background: Transmembrane protein 43 (TMEM43) is a phylogenetically highly conserved and ubiquitously expressed protein with unknown function. The protein contains four transmembrane domains located in the inner nuclear envelope and the endoplasmic reticulum (ER). A large acidic domain located between the first and second transmembrane domains, with unknown function, is exposed to the ER lumen. TMEM43-c.1073C>T is a rare fully penetrant mutation that leads to arrhythmogenic right ventricular cardiomyopathy type 5 (ARVC5). ARVC5 is associated with myocardial fibrosis, fibrofatty replacement and progressive loss of right ventricular myocardial tissue and severe arrhythmias causing sudden cardiac death (SCD) especially in males. The pathomechanism of ARVC5 is not well understood. Methods: We isolated and cultivated primary dermal fibroblasts of three different individuals carrying TMEM43-c.1073C>T (p.S358L). Proteins were isolated from cell cultures and analysed by Orbitrap mass spectrometry. Proteome data of the mutation carriers were compared to TMEM43 wildtype control fibroblasts. Additionally, TMEM43-p.S358L and control fibroblasts were investigated by transmission electron microscopy (TEM). Results: A total of 9 proteins were upregulated in fibroblasts expressing TMEM43-p.S358L (p<0.003). Of note, proteins involved in fatty acid metabolism, such as acyl-coenzym A (CoA) thioesterase 1 encoded by the gene ACOT1, and Malonate-CoA ligase encoded by ACSF3 were strongly upregulated (FC>3 or >2, respectively). ACOT1 catalyses hydrolysis acyl-CoAs to long chain fatty acids and CoA. ACSF3 catalyses the formation of thioesters between fatty acids and CoA. ACOT1 and ACSF3 regulate the intracellular levels of free fatty acids and are expressed in the cardiomyocytes of the human myocardium. TEM images of TMEM43-p.S358L carriers show an accumulation of multilamellar vesicles, which may support the dysregulation of the lipid metabolism. Conclusion: The differentially regulated proteins in dermal fibroblasts and the accumulation of multilamellar vesicles suggest a dysregulation of the lipid metabolism by TMEM43-p.S358L, which may also have relevance for the development of myocardial fibrofatty replacement contributing to ARVC5.